802.3cs-2022 - IEEE Standard for Ethernet. (IEEE, 2022)
Super-PON optical subscriber access networks, which are in the family of Ethernet passive optical networks (EPONs), are defined in this amendment to IEEE Std 802.3-2022. Super-PON has a reach of up to 50 km and up to 1024 ONUs over a point-to-multipoint passive optical distribution network (ODN) through wavelength division multiplexing (WDM). A Super-PON ODN contains a passive wavelength router that determines the channels used by the ODN. This standard specifies the Super-PON Reconciliation Sublayer (RS), Physical Coding Sublayer (PCS), Physical Medium Attachment (PMA) sublayer, and Physical Medium Dependent (PMD) sublayer at a MAC data rate of 10 Gb/s in the downstream direction and of 10 Gb/s or 2.5 Gb/s in the upstream direction.
Keywords: Local area networks (Computer networks)